TINJAUAN YURIDIS TERHADAP PENJATUHAN SANKSI PIDANA BAGI PELANGGAR PEMBATASAN SOSIAL BERSKALA BESAR DI MASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Aslamiah, Futri; Rahmadan, Davit; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The State of Indonesia is a state based on law (rechtsstaat) not based on power (machtsstaat). Indonesia is a state based on Pancasila and the 1945 Constitution. It is expressly stated in